Spatial load forecasting using a demand propagation approach - Melo, J. D. [UNESP]; Carreno, E. M.; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
A method for spatial electric load forecasting using multi-agent systems, especially suited to simulate the local effect of special loads in distribution systems is presented. The method based on multi-agent systems uses two kinds of agents: reactive and proactive. The reactive agents represent each sub-zone in the service zone, characterizing each one with their corresponding load level, represented in a real number, and their relationships with other sub-zones represented in development probabilities. The proactive agent carry the new load expected to be allocated because of the new special load, this agent distribute the new load in a propagation pattern. The results are presented with maps of future expected load levels in the service zone. The method is tested with data from a mid-size city real distribution system, simulating the effect of a load with attraction and repulsion attributes. The method presents good results and performance. © 2011 IEEE.
Keywords: agent; distribution planning; knowledge extraction; land use; multi-agent systems; Spatial electric load forecasting; Demand propagation; Distribution systems; Expected loads; Knowledge extraction; Load levels; Local effects; Propagation pattern; Reactive agent; Real distribution; Real number; Spatial load forecasting; Electric load distribution; Electric loads; Forecasting; Intelligent agents; Local area networks; Multi agent systems; Electric load forecasting